Mirabegron, A Selective β3-Adrenoceptor Agonist Causes an Improvement in Erectile Dysfunction in Diabetic Rats - Yilmaz-Oral, Didem; Kaya-Sezginer, Ecem; Askin, Dilan; Hamurtekin, Yesim; Gur, Serap (Experimental and Clinical Endocrinology & Diabetes, 2019)
Aim To investigate the possible beneficial effect of mirabegron [a selective β3-adrenoceptor (AR) agonist] treatment on erectile dysfunction (ED) in streptozotocin-induced diabetic rats.Methods Sprague-Dawley rats (n=20) were divided into two groups: control group and streptozotocin-induced diabetic group. In vivo erectile responses were evaluated after intracavernosal injection of mirabegron (0.4 mg/kg) in rats. The relaxation responses to electrical field stimulation (EFS, 10 Hz), sodium nitroprusside (SNP, 10 nM) and sildenafil (1 μM) of corpus cavernosum (CC) strips were examined after the incubation with mirabegron (10 μM). β3-ARs expression and localization were determined by Western blot and immunohistochemical analyses in CC tissue.Results In vivo erectile responses of diabetic rats [intracavernasal pressure (ICP) / mean arterial pressure, 0.17±0.01] were decreased, which were restored after administration of mirabegron (0.75±0.01, P<0.001). The basal ICP (7.1±0.6 mmHg) in diabetic rats was markedly increased after mirabegron (36.1 ±5.4 mmHg, P<0.01). Mirabegron caused markedly relaxation in diabetic rat CC after phenylephrine precontraction. The relaxation responses to EFS and sildenafil were reduced in diabetic CC, which were increased in the presence of mirabegron. Mirabegron enhanced SNP-induced relaxation response in both groups. The expression and immunoreactivity of β3-ARs localized to CC smooth muscle were observed in control and diabetic rats.Conclusions This is the first study to show that intracavernosal administration of mirabegron improved erectile function and neurogenic relaxation of CC in diabetic rats. These results may be supported by further studies using combinations of mirabegron and phosphodiesterase type 5 (PDE5) inhibitors for the treatment of diabetic ED, especially in patients who do not respond to PDE5 inhibitor therapy.
Keywords: corpus cavernosum; erectile dysfunction; intracavernosal pressure; mirabegron; diabetes.